Corticosteroid phobia: a questionnaire study using TOPICOP score - Choi, Ellie (Singapore Med J, 2020)
INTRODUCTION: Topical corticosteroids (TCS) are commonly used in dermatology for their anti-inflammatory action. The recent development of the TOPICOP© (Topical Corticosteroid Phobia) scale to assess steroid phobia has made the quantification and comparison of steroid phobia easier. The objective of this study was to assess the degree of steroid phobia at our institute and identify sources from which patients obtain information regarding TCS. METHODS: A cross-sectional survey was performed of dermatology patients regardless of steroid use. TOPICOP scale was used for the survey. Sources from which patients obtained information were identified and their level of trust in these sources assessed. RESULTS: 186 surveys were analysed. The median domain TOPICOP subscores were 38.9% (interquartile range [IQR] 27.8%–50.0%, standard deviation [SD] 24.4%) for knowledge and beliefs, 44.4% (IQR 33.3%–66.7%, SD 24.4%) for fears and 55.6% (IQR 33.3%–66.7%, SD 27.2%) for behaviour. The median global TOPICOP score was 44.4% (IQR 33.3%–55.6%, SD 17.6%). Female gender was associated with higher behaviour, fear and global TOPICOP scores. There was no difference in the scores based on disease condition, steroid use, age or education. Dermatologists were the most common source of information on topical steroids and trust was highest in dermatologists. CONCLUSION: The prevalence of steroid phobia in our dermatology outpatient setting was moderately high, with gender differences. Dermatologists were the most common source of information on TCS, and it was heartening to note that trust was also highest in dermatologists. Strategies to target steroid phobia should take into account these factors.